The KAJIAN IMPLEMENTASI PRINSIP DESAIN INKLUSI PADA RUANG PUBLIK, STUDI KASUS ALUN-ALUN SIDOARJO - dwiputri, marianne tunggadewi juluk (Universitas Ciputra Surabaya, 2024)
Alun-alun is a shared space that functions as a reception room for public. Because it is public space, alun-alun must be designed to be friendly for people with disabilities and the elderly. However, unfortunately, most public spaces in Indonesia were built without considering access for people with disabilities and the elderly. A design approach with inclusive principles was introduced as an equality-based approach where people with special needs such as people with disabilities and the elderly can explore every building and public space with a feeling of safety, comfort and confidence. The method used is a qualitative research method with a descriptive approach. The data collection technique was collected by direct observation in alun-alun Sidoarjo. The data obtained was then analyzed based on the inclusive design principles of Hawkins and friends. From the results of the study on the application of inclusive design, it can be seen that the Sidoarjo city square or alun-alun has not fully implemented the principles of inclusive design properly and correctly.